Kredibilitas Dakwah dalam Ruang Publik Digital Berbasis Algoritma Studi Penguatan Literasi Digital bagi Da’i dan Masyarakat - Bridav Hayati; M.Alawy Farhan Yahya; Reva Intan Zakiah; Ali Hasan Siswanto (Yayasan Dinamika Ilmu Banyuwangi, 2025)
The rapid expansion of algorithm-driven digital platforms has reshaped the epistemic landscape of Islamic da'wah. In this environment, the credibility of religious messages is no longer determined solely by scholarly authority, but increasingly by the logic of algorithmic visibility, audience engagement patterns, and the performative attributes of digital preachers. This study examines how da'wah credibility is constructed, negotiated, and contested within the algorithmic public sphere, and how digital literacy functions as a critical mediating factor for both preachers and audiences. Using a qualitative phenomenological approach, data were collected through in-depth interviews, digital observations, and documentation involving ten digital preachers, fifteen active social-media users, and two digital-literacy experts. The results indicate that algorithmic amplification favors emotional, sensational, and engagement-oriented religious content, often marginalizing substantive and scholarly-based da'wah. The study also reveals significant gaps in digital literacy among both preachers and audiences, contributing to the spread of religious misinformation and the emergence of popularity-based religious authority. This research contributes a novel integrative model that links credibility, algorithmic dynamics, and digital literacy within the digital da'wah ecosystem. The findings underscore the urgency of strengthening digital-literacy programs to maintain epistemic integrity, enhance critical consumption of religious content, and support responsible Islamic communication in an increasingly algorithm-governed public sphere.